Applications of ribosomal RNA gene restriction pattern analysis and pulsed-field gel electrophoresis in distinguishing Salmonella welterveden isolates in Malaysia. - Goh, Yee-Ling; Puthucheary, S.D.; Thong, K.L. (2000)
A representative sample of 20 isolates of Salmonella weltevredenstrains from stool cultures ofpatients admitted at the University Hospital, Kuala Lumpur, Malaysia were analyzed. All the strains weresusceptible to ampicillin, ceftriaxone, ciprofloxacin, chloramphenicol, tetracycline, trimethoprim, gentami-cin and co-trimoxazole. Ribosomal RNA gene restriction pattern analysis of PstI-digested DNA gave threeribotypes while pulsed-field gel electrophoresis (PFGE) analysis of XbaI-digested DNA gave ten distinctprofiles. PFGE was more discriminative than ribotyping in distinguishing the strains. The majority of thestrains analyzed were very closely related with similarity coefficient values ranging from 0.8 to 1.0. BothPFGE and ribotyping could distinguish one of the strains which was obtained from a patient following abone marrow transplant for β-thalassemia major, indicating that this particular strain was unrelated to therest of the strains from patients with acute gastroenteritis